Lebanon : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
The report highlights IMF's projections and estimates of Lebanon's central government operations, revenue and grants, and expenditure by economic classification, government debt, monetary survey, commercial bank interest rates on Lebanese pound transactions and U.S. dollar transactions during 2000-05; interest rates on treasure bills, size distribution of deposits, consolidated balance sheets of the commercial banks, 2000-05; nominal and real effective exchange rates, sovereign international bond insurance, 2000-05; selected indicators of economic activity, 2000-05; government expenditure by function, 2000-04; consumer price index, 2000-February 2006; et cetera.